Environmental Impact of Food Packaging Materials: A Review of Contemporary Development from Conventional Plastics to Polylactic Acid Based Materials - Ncube, Lindani Koketso; Ude, Albert Uchenna; Ogunmuyiwa, Enoch Nifise; Zulkifli, Rozli; Beas, Isaac Nongwe (Materials, 2020)
Plastics have remained the material of choice, and after serving their intended purpose, a large proportion ends up in the environment where they persist for centuries. The packaging industry is the largest and growing consumer of synthetic plastics derived from fossil fuels. Food packaging plastics account for the bulk of plastic waste that are polluting the environment. Additionally, given the fact that petroleum reserves are finite and facing depletion, there is a need for the development of alternative materials that can serve the same purpose as conventional plastics. This paper reviews the function of packaging materials and highlights the future potential of the adoption of green materials. Biopolymers have emerged as promising green materials although they still have very low market uptake. Polylactic acid (PLA) has emerged as the most favoured bioplastic. However, it is limited by its high cost and some performance drawbacks. Blending with agricultural waste and natural fillers can result in green composites at low cost, low greenhouse gas emissions, and with improved performance for food packaging applications. The continent of Africa is proposed as a rich source of fibres and fillers that can be sustainably exploited to fabricate green composites in a bid to achieve a circular economy.